2019
DOI: 10.14814/phy2.13998
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nrf2 deficiency on mitochondrial oxidative stress in aged skeletal muscle

Abstract: Oxidative stress and mitochondrial dysfunction are associated with the aging process. However, the role of nuclear factor erythroid 2 ‐related factor 2 (Nrf2) in skeletal muscle during aging remains to be clarified. In the current study, we assessed whether the lack of Nrf2, which is known as a master regulator of redox homeostasis, promotes age‐related mitochondrial dysfunction and muscle atrophy in skeletal muscle. Here, we demonstrated that mitochondrial 4‐hydroxynonenal and protein carbonyls, markers of ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 26 publications
6
55
0
1
Order By: Relevance
“…Previously, most literature held the opinion that aging results in impaired function of Nrf2 in skeletal muscle [18,27], which was based on studies in other tissues, such as Macaca mulatta vascular endothelial/smooth muscle [28], rat kidney [29], and mice myocardial cells [23]. However, several previous studies have investigated the effect of aging on the expression of Nrf2 and its downstream cytoprotective genes in the skeletal muscle but the results were inconsistent [27,30]. In recent years, increasing studies have recognized that expression of Nrf2 and its downstream genes in the skeletal muscle can be activated by physical exercise [27,31].…”
Section: Agingmentioning
confidence: 99%
“…Previously, most literature held the opinion that aging results in impaired function of Nrf2 in skeletal muscle [18,27], which was based on studies in other tissues, such as Macaca mulatta vascular endothelial/smooth muscle [28], rat kidney [29], and mice myocardial cells [23]. However, several previous studies have investigated the effect of aging on the expression of Nrf2 and its downstream cytoprotective genes in the skeletal muscle but the results were inconsistent [27,30]. In recent years, increasing studies have recognized that expression of Nrf2 and its downstream genes in the skeletal muscle can be activated by physical exercise [27,31].…”
Section: Agingmentioning
confidence: 99%
“…This can be achieved by overexpressing or silencing genes of mitochondriogenesis, or genes required to synthesize the mTORC1 complex as well as specific, step-dependent autophagy and mitophagy genes while measuring the efficacy of gene silencing in these experimental conditions. As a matter of fact, knockdown of NRF2 blocks mitochondriogenesis [ 44 , 45 , 46 ]. Many more studies about genetic manipulation of lysosomal activity are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [128] found that the upregulation of Nrf2 expression could alleviate oxidative stress and DNA damage and inhibit the p53-p21 p16-rb signaling pathway, thereby slowing cell aging. Nrf2 can regulate mitochondrial biogenesis and kinetics to maintain muscle mass and function, and its deficiency with aging increasingly promotes age-related skeletal muscle mitochondrial dysfunction and muscle atrophy [129,130]. Study also found that Nrf2 activation could inhibit age-related inflammatory responses and oxidative stress and delay the occurrence of aging and age-related diseases [131].…”
Section: Nuclear Factor-e2-related Factor 2 (Nrf2) Signalingmentioning
confidence: 94%